Pengaruh Kinerja Keuangan terhadap Kebijakan Dividen dengan Ukuran Perusahaan sebagai Variabel Moderasi - Almarya Okta Egidiya Rusma; Hesty Juni Tambuati Subing (Journal of Accounting, Management, and Economics Research (JAMER), 2024)
This study looks at how company size (SIZE) moderates the effects of profitability (ROI), liquidity (CR), and leverage (DER) on dividend policy (DPR) in food and beverage firms listed on the Indonesia Stock Exchange between 2017 and 2021. Purposive sampling is the procedure used in the sampling approach. This study's sample comprised sixteen companies listed on the Indonesia Stock Exchange. Multiple regression and moderated regression are the analysis techniques employed, with a 5% significance level. The study's pre-moderation results demonstrate the significant influence of the variables Profitability (ROI) and Leverage (DER) on Dividend Policy. The study's post-moderation results demonstrate the significant influence of Liquidity (CR), Leverage (DER), and Company Size (Size) on Dividend Policy. The executive. The managerial implications in this study are that management needs to set clear, realistic financial performance targets to ensure that the company is able to achieve sufficient to support dividend policy, and large companies can take advantage of economies of scale to improve financial performance, which in turn can support a larger dividend policy stable. Management must ensure efficient cash flow management to support dividend payments.